Forest beetles associated with cork oak and fomes fomentarius fungi in the Collo massif (Skikda), Algeria - Marniche, Faiza (Acta silvae et ligni, 2024)
A study conducted in an unburned cork oak forest located in the Collo Massif (Skikda), northwestern Algeria, resulted in the capture of 385 beetles in 2015 and 545 beetles in 2016 at three sub-stations, using Barber pitfall traps. The study lasted three months, from April to June, over two consecutive years. Additionally, using the carpophores method on Fomes fomentarius (Linné) (Fries, 1849), a total of 3,017 beetle specimens were obtained in 2015 and 3,107 beetle specimens in 2016, observed over the same three-month period around the three unburned sub-stations (Oued Agouf, Ain Fegoum and El Maktoua). The first observation concerning the Erotylidae family is that they are poorly known in North Africa, including Algeria, where published data on this subject is scarce. This study also revealed the presence of the species Triplax melanocephala (Latreille, 1804), which is rarely observed in Algeria. This species was recorded on the tinder fungus Formes fomentarius, with 30 individuals and 71 individuals counted in the Barber pitfall traps.
Keywords: bukova kresilka; Coleoptera; Erotylidae; Formes fomentarius; gozdovi plutovega hrasta; Triplax melanocephala